Religious Ideology and the Roots of the Global Jihad - Turner, J. author. aut Link
VII, 209 p.
Keywords: The events of 9/11 prompted questions as to the origins, nature and purpose of international jihadist organisations. In particular, why had they chosen to target the US and the West in general? Turner's book provides a unique, holistic insight into these debates, taking into account historical perceptions and ideology as key factors.